Assessing Recorded Lectures Effectiveness for Enhancing Grammar Mastery in a Flipped Classroom Model - Ahsin Fahmi Mubarok; Fitria Nur Hamidah; Mochammad Abdullah Salim; Rendhi Fatrisna Yuniar (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Examining recorded lectures’ effectiveness to teach grammar in the context of flipped classroom model has not been widely research. Furthermore, this type of teaching has not been frequently used in the research area which applies English for Specific Purpose (ESP) materials that require special treatment in teaching grammar. This study, therefore, aims to uncover the unknown research findings by implementing quasi experimental research by involving two classes in Mechanical Engineering department. Both classes were given pre-test before treatment to ensure the similarity of initial grammar skills and post-test after treatment to know the impact of recorded lectures in flipped classroom model for students in experimental group. Data gained through independent t-test from SPSS indicated that there was a significant impact of the treatment on students’ mastery in grammar proven by the significant value of 0.05 (above 0.05) As this type of teaching has been proven to be effective for teaching grammar especially in the context of ESP, lecturers who teach in the same setting are suggested implement recoded lecturers.